A Study on Applications of Cognitive Computing in the Internet of Things - Chawan, Ashutosh Rao Chawan Umesh Rao; Vallish, Parikshith (International Journal of Computer Sciences and Engineering, 2025)
The introduction of the Cognitive Approach of Computing would lead to a comprehensive and better decisionmaking system. This approach of cognitive computing on the Internet of Things is called Cognitive IoT or CIoT. This paper focuses on various different kinds of applications of Cognitive Computing in the field of IoT. The goal of Cognitive IoT is to make computers understand people by trying to recreate how the neocortex in our brain works to make them think like humans. These fields are interdependent as the computer requires numerous data points. With a collection of other devices performing the same task, their results can be used as information for the system to learn. The Internet of Things' concept of a "system of systems" helps Cognitive Computing's core plan to simulate the human brain move forward.